The Performance of ZnOCN4 in POMSE Treatment Using Photocatalytic Reactor - Mohd Jaafar, Nur Suhaika Afza; Md Rizal, Nurul Syafeka (Multidisciplinary Applied Research and Innovation, 2023)
This paper reports on the performance of different load of ZnO-CN 4 in POMSE treatment using Membrane Photocatalytic Reactor (MPR). Palm oil mill secondary effluent (POMSE) has high color intensity, turbidity and organic load of biochemical oxygen demand which still not achieved the discharged requirement by department of environment and led to detrimental to the aquatic life. Photocatalysis process is one of the promising methods in wastewater treatment due to itself advantages. Three different weight of ZnO-CN4 which is 0.09 g, 0.2 g and 0.4 g were used in this experiment using membrane photocatalytic reactor (MPR). The sampling of the sample were carried out from 0 to 60 minutes at 10 minutes interval. The treated samples were treated for colour. From this experiment, it was found that the 0.09 g of ZnO-CN4 give the best performance.